Data envelopment analysis : a comprehensive text with models, applications, references and DEA-Solver software - Cooper, William W; Seiford, Lawrence M; Tone, Kaoru (Kluwer Academic Publishers, 2000)
In a relatively short period of time Data Envelopment Analysis (DEA) has grown into a powerful quantitative, analytical tool for measuring and evaluating performance.It has been successfully applied to a host of different entities engaged in a wide variety of activities in many contexts worldwide.